A case of eosinophilic granuloma of the skull in an adult man: a case report - Kitsoulis, Panagiotis V (BioMed Central, 2009)
Eosinophilic granuloma is very rare benign bone tumor which presents in more than 90% in children under the age of ten. There is predominance for males. It is usually found at flat and long bones. The skull and vertebral spine is often affected. We report a case of 57 year-old man who gradually developed local pain at his skull and orbit. A soft, movable, palpable and tender mass was found at the left temporal bone. The pain deteriorated after an accidental injury at skull and remained so. The clinical examination revealed no pathological findings. The patient was a doctor who smoked and consumed alcohol daily. He had a history of cardial infraction and psoriatic arthritis. X-rays and CT revealed a round lytic defect at the skull. Its borders were sharp and its size was 1.6 × 1.8 cm. No periostic reaction or bone formation was noted. Scintigraphy depicted a lytic lesion without radionuclide enhancement. Thus we suspected an eosinophilic granuloma. An attempt to excise the tumor failed as it had already eroded the underlying temporal bone. The external meninga was affected but not the internal one. Histological diagnosis with dominance of Langerhans cells set the diagnosis. A second surgery was done and the eosinophilic granuloma was extracted. After eight months the gap was bridged with plastic heterologous transplant. After the curettage the patient received antibiotics and five cycles of radiotherapy. The aesthetic result was excellent. The patient's head has a normal hairy appearance. No tenderness, swelling or recurrence is recorded until now. Eosinophilic granuloma is of unknown aetiology but uncontrolled proliferation of Langerhans cells, previous inflammations or tumors and autoimmune disorders are suspected. Due to the co-existence of psoriatic arthritis and eosinophilic granuloma to our patient we assume that an autoimmune mechanism is probable.